Efficacy and Safety of Antioxidants in Complex Therapy of Infectious Diseases in Frequently Ill Children - M. L. Babayan (Вопросы современной педиатрии, 2013)
Acute respiratory infections are the most common diseases among pre-school and school children. Special group of frequently ill children demands additional rehabilitation measures after endured diseases. The author provides a review of Russian investigations on clinical efficacy of anti-oxidative polyvitamin drug among frequently and protractedly ill children. β-carotene, ascorbic acid and vitamin E are included into the composition of this drug. The received data strongly suggest that usage of this polyvitamin as a non-specific medicine to prevention and complex therapy of acute respiratory infections is safe and efficient.